PENATAAN KAWASAN WISATA AIR TERJUN RIAM AMPANGK DI DESA PISAK, KECAMATAN TUJUHBELAS, BENGKAYANG - Esyandra, Satria Ergi; Mustikawati, Mustikawati; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
The Riam Ampangk Waterfall Tourism Area in Pisak Village, Tujuhbelas District, Bengkayang Regency has high ecological and topographical potential. However, the condition of the facilities, infrastructure, and environment within the existing Riam Ampangk Waterfall Tourism Area does not yet meet the minimum tourism business requirements as stipulated in the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia No. 04 of 2021. This study aims to develop a spatial planning concept for the area that complies with the applicable regulations. The “4A” framework (attraction, accessibility, amenities, ancillary) is used to assess the feasibility of the tourism area. Data were obtained through field observations, interviews, and literature studies, which were then used to formulate zoning, circulation, facility layout, and adaptive structural designs. The main strategies in this arrangement include providing adequate facilities and infrastructure, ensuring that built-up areas do not dominate the site, and implementing developments that minimally alter the existing site conditions. This planning is expected not only to enhance the area’s competitiveness but also to serve as a model for architectural site design that attracts tourists while preserving the surrounding natural environment.